Parameter Effects of the Hydrostatic Propulsion Drive System on the Operation Accuracy of a Tamping Machine. (October 2019) - Wang, Wenlin; Cai, Xiong; Zhou, Zirong
Abstract: A dynamic mathematical model of the hydrostatic propulsion drive system of a tamping machine is established in this study, and a simulation model is built in the AMEsim software environment using the mathematical model. Parameter effects of the hydrostatic propulsion drive system on the operation accuracy of the tamping machine are analysed. Simulation results show that the effective moment of inertia of the powertrain and the oil volumetric elastic modulus have obvious influences on the operation accuracy of the tamping machine, the effect of the total volume of the high-pressure circuit of the hydraulic system on the displacement accuracy is not obvious, but it has some influence on the velocity amplitude. The models established and results obtained in this work are of significance and instructive for design optimization and maintenance of tamping machines.